The use of Egeria densa in understanding the cellular movement at the micro level of prospective science teachers - Abdurrahman Sefalı; Bilge Öztürk (Journal of Science Learning, 2024)
This study aims to help students learn cytoplasmic flow movement by using Egeria densa as a model. The study was conducted with six prospective science teachers studying at Bayburt University's Faculty of Education Science Teaching Undergraduate Program. As a data collection tool, a form containing questions to obtain prospective science teachers' knowledge of the concept of living things and the common characteristics of living things was used. The content analysis method was used to analyze the data. As a result of the findings, it was determined that although the prospective science teachers had sufficient knowledge about the vitality feature, they could not explain the movement, which has the vitality feature in detail. In addition, it was determined that the prospective science teachers could explain the cellular movement, which they had difficulty understanding at the micro level, by using Egeria densa as a model. Therefore, it can be said that using Egeria densa as a model for prospective science teachers to make sense of movement at a micro level is helpful.